Récit, disciplines, savoirs - Gilbert, Jacques Athanase (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
How to situate narrative in the field of knowledge? Can it be understood technically by grammatization? From Heidegger to Wittgenstein, this article explores the potential of narrative disciplinary order.